2014
DOI: 10.1111/lam.12301
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Tomato mosaic virus disease in tomato plants by deep ultraviolet irradiation using light-emitting diodes

Abstract: Disease caused in tomato plants by resistance-breaking Tomato mosaic virus (ToMV) could be suppressed by ultraviolet (UV)-B irradiation using light-emitting diodes (LEDs). This paves the way for the future management of plant viral diseases using deep UV LEDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…In the present study, the degree of rice leaf blight was significantly lower in the M. → UV-B treatment group than in the M. treatment group, although the OsLOX2 gene expression in the former was lower than that in the latter. This result indicated that the UV-B radiation supplied after M. oryzae inoculation did not aggravate leaf blight possibly because UV-B radiation slows down disease progression, inhibits the expansion of lesions, and weakens the growth of pathogens (Matsuura and Ishikura 2014). No significant difference was found between the PR contents in the M. → UV-B and M. treatment groups, indicating that UV-B radiation did not increase stress tolerance of M. oryzae-infected leaves.…”
Section: Discussionmentioning
confidence: 84%
“…In the present study, the degree of rice leaf blight was significantly lower in the M. → UV-B treatment group than in the M. treatment group, although the OsLOX2 gene expression in the former was lower than that in the latter. This result indicated that the UV-B radiation supplied after M. oryzae inoculation did not aggravate leaf blight possibly because UV-B radiation slows down disease progression, inhibits the expansion of lesions, and weakens the growth of pathogens (Matsuura and Ishikura 2014). No significant difference was found between the PR contents in the M. → UV-B and M. treatment groups, indicating that UV-B radiation did not increase stress tolerance of M. oryzae-infected leaves.…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, Demkura and Ballaré (2012) reported that UVR8 plays a key role in mediating the effects of UV-B radiation on pathogenicity by controlling expression of the sinapate biosynthetic pathway. Inactivation of pathogens by exposure to UV light is a well-known method of crop protection (Demkura and Ballaré 2012;Matsuura and Ishikura 2014;Nigro et al 1998). However, irradiation with UV light has limited applications because of its harmful effects on workers, such as injury to the skin or eye upon direct exposure (Young 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Suthaparan et al (2012) found a significant reduction in disease severity and conidial production of rose powdery mildew after UV irradiation that included wavelengths below 290 nm, but not when these wavelengths were filtered out by cellulose diacetate foil, indicating a possible role of UV-B wavelengths between 280 and 290 nm in not only eliciting defensive responses in plants, but also suppressing spore production of the fungus P. pannosa. Interestingly, Matsuura and Ishikura (2014)…”
Section: Discussionmentioning
confidence: 99%
“…pannosa . Interestingly, Matsuura and Ishikura (2014) reported that infection of tomato mosaic virus was suppressed in tomato plants by irradiating with narrow‐band LED UV‐B (280–290 nm). In future experiments, application of LED UV‐B could eliminate UV‐C wavelengths to evaluate more precisely the effects of UV‐B irradiation on induction of host resistance and on the direct suppression of fungal pathogens.…”
Section: Discussionmentioning
confidence: 99%